SOCIAL CAPITAL RECONSTRUCTION ON RESILIENCE BUILDING OF COMMUNITY CADRES BASED ON GEDSI - Rizkia, Arindini Ayu Kisvi; Setiadi, Elly Malihah; Nurbayani K., Siti (GoAcademica Research dan Publishing, 2025)
This study analyzes the social capital of community mobilization cadres in Antapani Sub-district, which serve as intermediaries between the community and the government in meeting the needs of urban communities. The main focus of this study is on the reconstruction of social capital towards the resilience of community mobilizers based on Gender Equity, Disability, and Social Inclusion (GEDSI). This research was conducted using the phenomenological method involving 3 stages of research. The research shows that community activist cadres in Antapani sub-district have social capital that can be reconstructed based on gender equity, disability, and social inclusion. The reconstruction of social capital is trust, social networks, and norms. The study identified a deep need for additional training to improve advocacy skills and regulatory understanding. Gender differences affect how cadres build networks and trust. Empowerment through social inclusion programs and a better understanding of disability are critical to improving cadres' effectiveness in serving marginalized groups. Reconstructing social capital with a GEDSI perspective is expected to strengthen the capacity of cadres to address various community needs, improve access, and build better relationships with diverse community groups. The findings highlight the need for a more inclusive and gender-equity-based approach to enhance the role and effectiveness of community cadres.